Program Psikoedukasi Mengatasi Bullying pada Anak Berkebutuhan Khusus di Sekolah Dasar Inklusi - Efendi, Nur Fitriyah; Widiyono, Aan (Universitas Nusantara PGRI Kediri, 2025)
This study aims to identify the forms and factors of bullying, strategies for overcoming bullying and deepening the understanding of students at SDN 1 Sowanlor regarding the dangers of bullying. This study uses a qualitative method with a phenomenological approach. Data were collected through observation, interviews and documentation techniques. The results of the study indicate that children with special needs who are categorized as slow learners, dyslexics and dysgraphia are victims of bullying. The forms of bullying experienced include verbal and physical bullying which are influenced by environmental factors and family conditions. To overcome this problem, researchers conducted a psychoeducation program using posters and powerpoint media about bullying. This program contributed significantly to fostering empathy and increasing students' awareness of the importance of mutual respect and stopping bullying behavior in the school environment.